Cholesteatoma of the auditory canal complicated by retroauricular abscess - Acuña Ramírez, Ashiria Reseda; Roig Ocampos, Jorge; Mena Canata, Carlos (Medicina Clínica y Social, 2024)
Cholesteatoma of the External Auditory Canal (CCAE) is a rare pathology. Its diagnosis is fundamentally clinical, based on imaging studies and final anatomopathological confirmation. Some cases can be asymptomatic and other cases can present complications such as facial paralysis, middle ear involvement, etc. Its treatment is surgical with a series of techniques called canaloplasties, which aim to remove the cholesteatomatous tissue and create a self-evacuation mechanism. We present the description of a case of cholesteatoma of the auditory canal complicated with retroauricular abscess in a young patient with congenital stenosis, discuss the relevant aspects regarding the clinic, differential diagnoses, and therapeutic options in a review of the available literature.
Keywords: cholesteatoma of the duct; duct stenosis; external ear